Post-Migration Outcomes and the Decision to Return: Processes and Consequences - Setrana, Mary Boatemaa (African Human Mobility Review, 2021)
This paper examines the decision-making processes of return migrants,especially since the 2001 introduction of government programmes to encouragethe return of skilled migrants who have the capacity to contribute their quota tothe development agenda of Ghana. Structured questionnaires were used togather information on the migration trajectories of 120 return migrants. Thiswas followed by interviews that primarily sought in-depth understanding of thedecision-making processes of the return migrants. The findings indicate thatthese migrants were motivated by, among other factors, the availability ofinvestment opportunities in Ghana, completion of education abroad, loss of jobsabroad, the decision to join family, feeling homesick and difficulty in integratingabroad. The paper recommends that home country governments should developconducive policies appropriate for addressing the needs of the categories ofreturnees based on their decisions for coming home and how their skills andresources could be channelled into development.